Alteration of Plasma Antithrombin III Levels in Ischemic Heart Disease - Yue, Robert H.; Gertler, Menard M.; Starr, Toby; Koutrouby, Russell (Thrombosis and Haemostasis, 1976)
The amount of anti thrombin III in plasma was determined quantitatively in 218 males between 45–60 years of age. The mean antithrombin III value was found to be low in the group with low risk for ischemic heart disease, intermediate in the group with high risk for ischemic heart disease and highest in the group with acute myocardial infarction. Concomitant study of kaolin-activated partial thromboplastin time revealed a sharp decrease in its mean value in the group with acute myocardial infarction. The high correlation between antithrombin III and kaolin-activated partial thromboplastin time for the entire population suggests that the development of ischemic heart disease is a gradual process and that failure of the damping mechanism results as an acute event. These findings may be useful in the determination of the coagulation state of these patients.